Electrical impedance spectroscopy (EIS) technology for fouling detection in RO process - Chong, Qi Yun (Nanyang Technological University, 2022)
Electrical impedance spectroscopy (EIS) as a monitoring tool to detect the onset of membrane fouling in reverse osmosis (RO) processes has been widely studied. Its ability to achieve on-line early fouling detection non-invasively garnered interest to develop this tool to become an in-situ monitoring tool applicable in industrial scale. In this study, the feasibility of applying thin-film electrode in a laboratory RO-EIS system through assessing the adhesive and electrochemical properties of the thin-film electrodes and finally integrating the thin-film electrodes into an acrylic flat-sheet RO membrane test cell for fouling experiment. Several thin-film electrodes were tested for their adhesive strength to the substrate material through ultrasonic, immersion and tape tests. Their electrochemical properties were characterized by running cyclic voltammetry (CV) and EIS tests. A pair of electrodes, Au-Cr-PVD, were used for the fouling experiment using sodium alginate as model foulant and sodium chloride as background electrolyte. EIS signals obtained was found to correlate well with the changes in permeate flux. The electrochemical properties of the electrode fitted at the feed side was evaluated by running the CV and EIS tests after the crossflow filtration. The results produced were then compared with the electrochemical results before the fouling experiment.